2020
DOI: 10.3390/ijerph17020420
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Adolescents’ Relationships with Parents, Peers, and Teachers, Self-Efficacy, and Willingness to Intervene in Bullying: A Social Cognitive Approach

Abstract: We applied the Social Cognitive Theory to investigate whether parent–child relationships, bullying victimization, and teacher–student relationships are directly as well as indirectly via self-efficacy in social conflicts associated with adolescents’ willingness to intervene in a bullying incident. There were 2071 (51.3% male) adolescents between the ages of 12 and 17 from 24 schools in Germany who participated in this study. A mediation test using structural equation modeling revealed that parent–child relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…In prior meta-analysis, the strongest predictor of intention is self-efficacy [23]. Self-efficacy is a psychological mediator of health because it will lead one to practice disease prevention activities [24]. A person's self-efficacy is determined by their actions and experiences with their parents, their friends, and their teachers.…”
Section: Discussionmentioning
confidence: 99%
“…In prior meta-analysis, the strongest predictor of intention is self-efficacy [23]. Self-efficacy is a psychological mediator of health because it will lead one to practice disease prevention activities [24]. A person's self-efficacy is determined by their actions and experiences with their parents, their friends, and their teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Via a thorough literature review, Social Cognitive Theory (SCT) ( Bandura, 1982 ) was identified as being the fundamental theoretical framework for determining the likelihood of a person committing online shaming. SCT has been applied to both offline and online to investigate and clarify the acts of bullying and harassment ( Farooq et al, 2021 ; Bjärehed et al, 2021 ; Wachs et al, 2020 ; Xiao and Wong, 2013 ); investigated the impact of the community environment on the intention to share information in virtual communities ( Cai and Shi, 2020 ); investigated the factors that influence students’ intention to continue using blogs to learn ( Tsai and Cheng, 2012 ). According to SCT, human motivation and behaviour are extensively controlled by forethought, and this anticipatory control system includes expectations that may refer to the effects of a particular action ( Bandura, 1982 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, children and adolescents "with positive social relationships with parents, peers, and teachers benefit from these experiences and, therefore, are more likely to display better social, emotional and behavioral outcomes" (Wachs et al, 2020, p. 2). In addition, teachers who hold a positive relationship with their pupils may be more prone to promote an efficacious communication with them, encourage them, reinforce positive behaviors, and provide helpful feedbacks, which may foster pupils' self-efficacy and willingness to behave properly (Wachs et al, 2020).…”
Section: The Role Of the Relationship With Teachersmentioning
confidence: 99%